Particle-reinforced ceramic fiber paper and preparation method thereof

By using the combination of ceramic short fibers and inorganic particles in the preparation of ceramic fiber paper, the problem of difficulty in uniform dispersing of ceramic fibers in the pulp is solved, the performance improvement of ceramic fiber paper is achieved, and ceramic paper with high strength, heat insulation and flame resistance is prepared.

CN116770630BActive Publication Date: 2025-05-02HEFEI INNOVATION RES INST BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210289356.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-11
Filing Date
2022-03-22
Publication Date
2025-05-02
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

Ceramic fibers are difficult to disperse evenly in the pulp and easily settle, which limits the performance improvement of ceramic fiber paper.

Method used

Ceramic staple fibers are used to completely replace natural fibers, combined with inorganic particles to enhance them, and uniform dispersion and enhancement of ceramic fibers are achieved by using dispersants and inorganic particles during the heating molding process.

Benefits of technology

The proportion of ceramic fibers of ceramic fiber paper is improved, its comprehensive performance is enhanced, and the preparation of ceramic paper with uniform fiber distribution, high strength, good heat insulation effect and good flame resistance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116770630B_ABST
    Figure CN116770630B_ABST
Patent Text Reader

Abstract

The present invention discloses a particle-reinforced ceramic fiber paper and a preparation method thereof, wherein the ceramic paper comprises the following components in parts by weight: 1-100 parts of ceramic fiber, 0.5-5 parts of dispersant, and 1-10 parts of reinforcing particles. The preparation method of the ceramic paper comprises uniformly dispersing the ceramic fiber, reinforcing particles and dispersant in water, and heating and drying in a mold to obtain particle-reinforced ceramic fiber paper. The present invention preferably uses polyethylene glycol as a dispersant and an adhesive, and uses water as a dispersed phase, and ceramic paper can be formed without large-scale equipment, and the preparation process is simple and green. The ceramic paper product of the present invention has a smooth surface, stable quality, is easy to promote, and the reinforcing particles are highly designable, and have good application prospects in the fields of flame retardancy, heat insulation, wear resistance and functional films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic fiber paper preparation, and in particular to particle-reinforced ceramic fiber paper and a preparation method thereof. Background Art

[0002] Ceramic fiber is a fibrous lightweight refractory material with the advantages of light weight, high temperature resistance, good thermal stability, low thermal conductivity, low specific heat and resistance to mechanical vibration. Common ceramic fibers include basalt fiber, SiC fiber, etc., which have broad application prospects and development potential in aerospace, automobile, transportation and military fields.

[0003] Adding ceramic fibers during the preparation of paper is an effective means to improve the strength, wear resistance and flame retardancy of paper materials. In general, paper is prepared by using organic fibers to make pulp, and paper is obtained through operations such as papermaking and drying. Ceramic fiber paper is made by replacing some natural fibers with ceramic fibers in the ordinary papermaking process to form paper made of composite fibers. However, due to the problems of high density and poor bonding between fibers, the proportion of ceramic fibers in the pulp cannot be too high, which also restricts the further improvement of the performance of ceramic paper.

[0004] In recent years, research on ceramic paper has gradually emerged at home and abroad. Japan's Koto Corporation has developed a heat-resistant ceramic paper that can be used continuously at a temperature of 1000°C. However, the heat-resistant ceramic paper generally requires that the content of alumina and silica must not be less than 96%, and the alkali content is low, and the proportion of wood pulp will not be higher than 10%; and styrene-butadiene latex, vinyl chloride latex, phenolic emulsion, cationic starch, sodium silicate and sodium polyphosphate are used as binders; Chen Hongbing et al. blended natural polymers and inorganic clays, freeze-dried and dehydrated, and then used 40MPa high-pressure pressing to prepare nanopaper (CN103850152A); Cao Liyun et al. mixed nano-titanium, multi-walled carbon nanotubes, phenolic resin and natural fibers, shook, dispersed and made paper, and obtained nano-titanium reinforced paper-based friction materials (CN1033210878); Yang Fanshun et al. prepared paper ceramics by sintering after slurry and pulp blending (CN1041933048). The above methods can all achieve the preparation of nanoparticle-reinforced ceramic paper, but most of them require natural pulp as material and require special ceramic paper processing equipment, and the process is relatively cumbersome, thus limiting their application development. Summary of the invention

[0005] In order to improve the above technical problems, the present invention provides a ceramic paper, which comprises the following components in parts by weight: 1-100 parts of ceramic fibers, 0.5-5 parts of dispersants, and 1-10 parts of reinforcing particles.

[0006] According to an embodiment of the present invention, the mass ratio of the ceramic fiber to the reinforcing particles is (0.6-100):1, exemplified by 0.6:1, 1:1, 2:1, 5:1, 10:1, 30:1, and 100:1.

[0007] According to an embodiment of the present invention, the ceramic fiber is preferably a ceramic short fiber. Preferably, the ceramic fiber has a diameter of 1 to 20 μm and a length of 0.1 to 100 mm.

[0008] According to an embodiment of the present invention, the ceramic fiber can be basalt fiber, SiC fiber, Al 2 O 3 One of the fibers or a mixture of two fibers.

[0009] Preferably, when the ceramic fiber is a mixture of two fibers, the mixing ratio of the two fibers may be 1 to 10:1, exemplified by 1:1, 2:1, 5:1, 8:1, and 10:1.

[0010] According to an embodiment of the present invention, the particle size of the reinforcing particles is less than 50 μm, preferably insoluble particles with a particle size of less than 30 μm, exemplarily 500 mesh.

[0011] According to an embodiment of the present invention, the reinforcing particles include but are not limited to MAX phase powder, calcium carbonate (CaCO 3 ) powder, graphene oxide and other inorganic particles.

[0012] According to an embodiment of the present invention, the dispersant may be a polymer or ionic dispersant, for example, may be selected from at least one of polyethylene glycol, polyacrylamide, sodium dodecyl sulfate, and the like.

[0013] Preferably, the degree of polymerization of the polyethylene glycol is 1000-100000, exemplified by 1000, 5000, 10000, 100000.

[0014] According to an embodiment of the present invention, the thickness of the ceramic paper is 0.1 mm to 2 mm, exemplified by 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 1.7 mm, and 2 mm.

[0015] According to an embodiment of the present invention, the paper surface density of the ceramic paper is 200-800 g / m 2 , exemplified by 200 g / m 2 , 300g / m 2 , 400g / m 2 , 500g / m 2 , 600g / m 2 , 700g / m2 , 800g / m 2 .

[0016] According to an embodiment of the present invention, the ceramic paper has a tensile strength of 5 to 10 MPa, exemplified by 5 MPa, 7 MPa, 7.6 MPa, 8 MPa, 8.6 MPa, and 10 MPa.

[0017] The present invention also provides a method for preparing the ceramic paper, which comprises the following steps: injecting pulp comprising the above components into a ceramic fiber paper forming mold, heating and forming, and obtaining the ceramic paper.

[0018] According to an embodiment of the present invention, the concentration of the dispersant in the pulp is 0.1 wt% to 5 wt%, exemplified by 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, and 5 wt%.

[0019] According to an embodiment of the present invention, the mass ratio of ceramic fiber to reinforcing particles in the pulp is (0.6-100):1, exemplified by 0.6:1, 1:1, 2:1, 5:1, 10:1, 30:1, 100:1.

[0020] According to an embodiment of the present invention, the slurry further comprises a dispersed phase. For example, the dispersed phase is water.

[0021] According to an embodiment of the present invention, the concentration of the ceramic fiber in the pulp is 1-4wt%, exemplified by 1wt%, 1.5wt%, 2wt%, 3wt%, and 4wt%.

[0022] According to an embodiment of the present invention, the heating molding temperature is 50-90°C, exemplified by 50°C, 60°C, 70°C, 80°C, and 90°C; the heating molding time is 5-10h, exemplified by 5h, 8h, and 10h.

[0023] According to an embodiment of the present invention, the method for preparing the pulp comprises mixing a dispersed phase (such as water) with a dispersant to obtain a dispersant solution, and then dispersing reinforcing particles and ceramic fibers in the dispersant solution to prepare the pulp.

[0024] Preferably, the method for preparing pulp further comprises heating and stirring the pulp.

[0025] For example, the heating temperature is 60-80°C, exemplified by 60°C, 70°C, and 80°C.

[0026] For example, the stirring time may be more than 5 minutes.

[0027] According to an embodiment of the present invention, the method for preparing ceramic paper further comprises laying a substrate in a ceramic fiber paper forming mold so as to separate the ceramic paper from the mold after forming. For example, the substrate may be a polyimide film (PI film) or filter paper. Further, the ceramic fiber paper forming mold may be, for example, a culture dish.

[0028] According to an embodiment of the present invention, the method for preparing ceramic paper further comprises preheating the ceramic fiber paper forming mold. For example, the preheating temperature may be 60-80°C, exemplified by 60°C, 70°C, and 80°C.

[0029] According to an embodiment of the present invention, the method for preparing the ceramic paper further comprises separating the ceramic paper and the substrate after the ceramic paper is heated and formed to obtain the ceramic paper.

[0030] According to an embodiment of the present invention, the method for preparing ceramic paper includes the following steps: mixing a dispersed phase (such as water) with a dispersant, and then dispersing reinforcing particles and ceramic fibers in the above solution to form a pulp; transferring the pulp to a ceramic fiber paper forming mold and heating and forming it to obtain the ceramic paper.

[0031] The invention also provides application of the ceramic paper in the fields of aerospace, automobile, transportation and military.

[0032] Beneficial effects of the present invention:

[0033] (1) The present invention uses ceramic short fibers to completely replace natural fibers to prepare paper, thereby increasing the proportion of ceramic fibers in commercially available ceramic fiber paper and effectively bringing into play the excellent comprehensive performance of ceramic fibers (such as basalt fibers); the preparation method provided by the present invention solves the problem that ceramic fibers are difficult to disperse evenly and are easy to settle in paper pulp, and ceramic fiber paper can be easily prepared under laboratory conditions; the present invention innovatively adds inorganic particles during the preparation of ceramic fiber paper, which can further give ceramic fiber paper functionality under the condition of ceramic fiber loading to improve the performance of ceramic fiber paper. The preparation method of ceramic paper of the present invention provides guidance for the preparation of fiber-reinforced ceramic-based composite materials.

[0034] (2) The present invention provides a relatively simple papermaking method that completely uses ceramic fibers and inorganic reinforcing particles as raw materials, and produces a thin sheet of paper material that is flexible, wear-resistant, heat-insulating, and flame-retardant. At the same time, in order to further improve the performance or functionality of ceramic fiber paper, the present invention can add other particles to the pulp to form a ceramic fiber paper composited with ceramic fibers and functional particles.

[0035] (3) The thickness of the ceramic paper prepared by the present invention can be adjusted by increasing or decreasing the amount of ceramic fiber. After a large number of experiments, it was unexpectedly found that the thickness of the ceramic paper can be adjusted within the range of 0.1 mm to 2 mm with good effect. The ceramic paper prepared by the present invention has excellent properties such as uniform fiber distribution, good strength, and good thermal insulation effect. The paper surface density is 200 to 500 g / m 3 The tensile strength reaches 5-10MPa. The paper does not carbonize within 2 hours at 200℃, and only local carbonization occurs when burned in flames. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The figure is a schematic diagram of the preparation process of the pulp of the present invention.

[0037] Figure 2 Schematic diagram of pulp transfer and drying. DETAILED DESCRIPTION

[0038] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0039] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0040] Example 1

[0041] A method for preparing ceramic paper comprises the following steps:

[0042] Add 200 mL of deionized water to a beaker, weigh 1 g of polyethylene glycol with a degree of polymerization of 1000, add it to the beaker, and stir evenly; weigh 2 g of basalt fiber with a diameter of 10 μm and a length of 1 mm, add it to the beaker, and heat the beaker to 70°C in an oil bath, and stir it with a magnetic force for more than 5 minutes until the basalt fiber is evenly dispersed in the water to form a suspension. Keep the suspension heated and stirred, and take Ti 3 AlC 2 2g of powder is added to the suspension of basalt fiber in three times until the mixture is uniformly black to obtain pulp. Take a petri dish with a diameter of 10cm, lay a polyimide film on the bottom, and place it in an infrared oven to preheat to 60℃; take the pulp out of the oil bath and quickly transfer the pulp to the petri dish in the oven (minimize disturbance as much as possible to prevent fiber dispersion). Keep the oven at 60℃ for 8h, and take out the petri dish after drying the moisture. Remove the polyimide film from the surface of the ceramic paper to obtain nanoparticle-reinforced ceramic paper.

[0043] The thickness of the prepared ceramic paper was measured by a spiral micrometer, the mass was weighed by an electronic balance, the diameter was measured by a vernier caliper and the surface density was calculated, the tensile strength was measured by a mechanical testing machine according to ASTM D882-91, the water absorption was measured according to standard ASTM D5229, and the flame retardancy was tested at 200°C in a high temperature oven.

[0044] In this embodiment, the thickness of the ceramic paper measured by a micrometer is 0.2 mm, the fiber distribution is uniform, and the surface density of the paper is 400 g / m 2 The tensile strength reaches 6.5MPa, the water absorption rate is about 40%, the paper does not carbonize within 2h at 200℃, and only local carbonization occurs when burned in flames.

[0045] Example 2

[0046] A method for preparing ceramic paper comprises the following steps:

[0047] Add 100mL of deionized water to a beaker, weigh 2g of sodium dodecyl sulfate and add it to the beaker, stir evenly; weigh 2g of basalt fiber with a diameter of 10μm and a length of 5mm and add it to the beaker, and heat the beaker to 70℃ in an oil bath, and stir magnetically for more than 10min until the basalt fiber is evenly dispersed in the water to form a suspension. Keep the suspension heated and stirred, and add a total of 1g of calcium carbonate powder with a particle size of 20μm in 3 times while stirring magnetically, and stir until the mixed solution is uniformly milky white to obtain pulp. Quickly transfer the mixed solution to a culture dish in an oven (the culture dish is placed in the oven first to minimize disturbance and prevent fiber dispersion) and dry the water at 60℃ for about 7-8h. The bottom of the culture dish should be padded with PI film or filter paper to facilitate the complete removal of the ceramic paper. After heating, remove the polyimide film from the surface of the ceramic paper to obtain nanoparticle-reinforced ceramic paper.

[0048] The thickness of the prepared ceramic paper was measured by a spiral micrometer, the mass was weighed by an electronic balance, the diameter was measured by a vernier caliper and the surface density was calculated, the tensile strength was measured by a mechanical testing machine according to ASTM D882-91, the water absorption was measured according to standard ASTM D5229, and the flame retardancy was tested at 200°C in a high temperature oven.

[0049] The thickness of the ceramic paper prepared in this embodiment is about 0.25 mm, the fiber distribution is uniform, and the surface density of the paper is 573 g / m 2 The tensile strength reaches 7.7MPa, the water absorption rate is about 40%, the paper does not carbonize within 2h at 200℃, and only local carbonization occurs when burned in flames.

[0050] Example 3

[0051] A method for preparing ceramic paper comprises the following steps:

[0052] Add 200mL of deionized water to a beaker, weigh 1g of polyacrylamide and add it to the beaker, stir evenly; weigh 6g of SiC fiber with a diameter of 12μm and a length of 10mm and add it to the beaker, and heat the beaker to 70℃ in an oil bath, and stir it magnetically for more than 5min until the basalt fiber is evenly dispersed in the water to form a suspension. Keep the suspension heated and stirred, and add a total of 0.5g of graphene oxide powder with a sheet size of 20μm twice while stirring magnetically, and stir until the mixed liquid is uniformly black to obtain pulp. Take a Petri dish with a diameter of 10cm, lay a piece of filter paper on the bottom, and place it in an infrared oven to preheat to 80℃; take the pulp out of the oil bath and quickly transfer the pulp to the Petri dish in the oven (minimize disturbance as much as possible to prevent fiber dispersion). Quickly transfer the mixed liquid to the Petri dish in the oven to dry the water at 80℃ for about 9h. After the heating is completed, the polyimide film is removed from the surface of the ceramic paper to obtain the nanoparticle-reinforced ceramic paper.

[0053] The thickness of the prepared ceramic paper was measured by a spiral micrometer, the mass was weighed by an electronic balance, the diameter was measured by a vernier caliper and the surface density was calculated, the tensile strength was measured by a mechanical testing machine according to ASTM D882-91, the water absorption was measured according to standard ASTM D5229, and the flame retardancy was tested at 200°C in a high temperature oven.

[0054] The thickness of the ceramic paper prepared in this embodiment is 0.5 mm, the fiber distribution is uniform, and the surface density of the paper is 770 g / m 2 The tensile strength reaches 8.4MPa, the water absorption rate is about 40%, the paper does not carbonize within 2h at 200℃, and only local carbonization occurs when burned in flames.

[0055] Example 4

[0056] A method for preparing ceramic paper comprises the following steps:

[0057] Add 300 mL of deionized water to a beaker, weigh 2.5 g of polyethylene glycol with a degree of polymerization of 100,000, add it to the beaker, and stir evenly; weigh 2.5 g of basalt fiber with a diameter of 10 μm and a length of 5 mm, and 2.5 g of SiC fiber with a diameter of 12 μm and a length of 5 mm, add them to the beaker, and heat the beaker to 70°C in an oil bath, and stir magnetically for more than 5 minutes until the basalt fiber and SiC fiber are evenly dispersed in the water to form a suspension. Keep the suspension heated and stirred, and add a total of 1 g of Ti with a particle size of 5 μm in 3 times while stirring magnetically. 3 AlC 2Powder, stir until the mixture is uniformly black to obtain pulp. Take a Petri dish with a diameter of 10 cm, lay a polyimide film on the bottom, and place it in an infrared oven to preheat to 80°C; take the pulp out of the oil bath and quickly transfer the pulp to the Petri dish in the oven (minimize disturbance as much as possible to prevent fiber dispersion). Quickly transfer the mixed solution to the Petri dish in the oven to dry the moisture at 80°C for about 10 hours. After heating, remove the polyimide film from the surface of the ceramic paper to obtain nanoparticle-reinforced ceramic paper.

[0058] The thickness of the prepared ceramic paper was measured by a spiral micrometer, the mass was weighed by an electronic balance, the diameter was measured by a vernier caliper and the surface density was calculated, the tensile strength was measured by a mechanical testing machine according to ASTM D882-91, the water absorption was measured according to standard ASTM D5229, and the flame retardancy was tested at 200°C in a high temperature oven.

[0059] The thickness of the ceramic paper prepared in this embodiment is 0.4 mm, the fiber distribution is uniform, and the surface density of the paper is 700 g / m 2 The tensile strength reaches 9MPa, the water absorption rate is about 40%, the paper does not carbonize within 2h at 200℃, and only local carbonization occurs when burned in flames.

[0060] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A ceramic paper, characterized in that: The ceramic paper comprises the following components in parts by weight: 1-100 parts of ceramic fiber, 0.5-5 parts of dispersant, and 1-10 parts of reinforcing particles; The mass ratio of the ceramic fiber to the reinforcing particles is (2-30):1; The ceramic fiber is one of basalt fiber, SiC fiber, Al2O3 fiber or a mixture of two fibers; the diameter of the ceramic fiber is 10-20 μm and the length is 1-10 mm; The reinforcing particles are calcium carbonate (CaCO3) powder, Ti3AlC2, and graphene oxide inorganic particles; The dispersant is selected from at least one of polyethylene glycol and sodium lauryl sulfate; The paper surface density of the ceramic paper is 600-800g / m 2 ; The tensile strength of the ceramic paper is 7-10 MPa.

2. The ceramic paper according to claim 1, characterized in that: When the ceramic fiber is a mixture of two fibers, the mixing ratio of the two fibers is 1 to 10:

1.

3. The ceramic paper according to any one of claims 1 to 2, characterized in that: The thickness of the ceramic paper is 0.1 mm to 2 mm.

4. The method for preparing ceramic paper according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: injecting paper pulp including ceramic fiber, dispersant and reinforcing particle components into a ceramic fiber paper forming mold, heating and forming, and obtaining the ceramic paper.

5. The preparation method according to claim 4, characterized in that: The concentration of the dispersant in the pulp is 0.1 wt% to 5 wt%.

6. The preparation method according to claim 4, characterized in that: The mass ratio of ceramic fibers to reinforcing particles in the pulp is (2-30):

1.

7. The preparation method according to claim 4, characterized in that: The concentration of the ceramic fibers in the pulp is 1-4 wt %.

8. The preparation method according to claim 4, characterized in that: The heating and forming process is performed at a temperature of 50 to 90° C. and a heating and forming time of 5 to 10 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The method for preparing ceramic paper comprises the following steps: mixing a dispersed phase with a dispersant, dispersing reinforcing particles and ceramic fibers in the solution to prepare pulp; and transferring the pulp to a ceramic fiber paper forming mold and heating and forming the mold to prepare the ceramic paper.

10. Use of the ceramic paper according to any one of claims 1 to 3 and / or the ceramic paper prepared by the preparation method according to any one of claims 4 to 9 in the fields of aerospace, automobile, transportation and military.

Citation Information

Patent Citations

  • Nanometer paper material and preparation method thereof

    CN103850152A

  • High temp. resisting low thermoconducting flexible ceramics fibre composite paper and its making method

    CN1861901A